Socio-epidemiological Variables of Female Infertility in Camagüey Province - Rolando Rodríguez Puga; Yoánderson Pérez Díaz; Nurys Vázquez Rodríguez; Yanira González Ronquillo (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Background: female infertility is a term used to refer to a woman who has not been able to get pregnant after trying for at least a year by having unprotected sexual intercourse. Objective: to characterize some socio-epidemiological variables of female infertility in Camagüey province. Methods: a descriptive, cross-sectional study was carried out at the Ana Betancourt Mora Camagüey Provincial Gynecobstetric Teaching Hospital during the year 2021. The universe consisted of 304 patients diagnosed with infertility. The variables studied included: age group, type of infertility, municipality of origin, incidence rate, educational level, toxic habits, risk factors, and personal history. Data were expressed in numbers and percentages. Results: 30.9 % corresponded to the age group of 30 to 34 years, coming mostly from the Camagüey municipality (43.5 %), while Cespedes reached the highest incidence rate (13.8 %) per 1000 women with age range that could be admitted to the program. A high percentage had university studies (45.4 %) and pre-university studies (24.3 %), the consumption of coffee (24.0 %) and tobacco (14.5 %) predominated as toxic habits; as well as sexually transmitted diseases (24.7 %) and the use of contraception (21.1 %). Obesity (13.5 %) turned out to be the main personal history. Conclusions: female infertility is determined by several factors, including epidemiological ones, such as toxic habits, nutritional status, personal history, among others, mostly modifiable, which can be treated from Primary Health